ANALISIS USAHA PENGEMBANGAN PETERNAKAN AYAM BROILER DI KECAMATAN BANGKALA KABUPATEN JENEPONTO - Nur Atikah; P. Tandi Balla; Sumang Sumang; Muhammad Irfan Aryawiguna (Jurnal Agrisistem : Seri Sosek dan Penyuluhan, 2019)
Broiler chicken is a superior race as a result of the cross marriage between the male of White Cornish from England and the female of Plymouth Rock 12 from America. This marriage produces of chicken which have quick growth and high feed conversion into meat. However, they have low feed conversion into egg. The study aims to find out the farmers’ income from boiler chicken business. The study applied descriptive research method by analysing directly the boiler chicken farming in Bangkala District, Jeneponto Regency. The result of the business feasibility study showed that the investment cost was IDR 3,563,000, production cost was IDR 83,435,000, income (IDR 94,052,000), profit (IDR 7,837,000), R/C ratio (1.08), and B/C ratio (0.08). The conclusion of this study is the broiler chicken farming is beneficial and feasible to be developed.